2016
DOI: 10.5935/0004-2749.20160049
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile in conjunctival, lacrimal sac, and nasal specimens and conjunctival normalization time following external, endoscopic, and transcanalicular multidiode laser dacryocystorhinostomy

Abstract: Purpose: To compare the conjunctival, lacrimal sac, and nasal flora cultures and conjunctival normalization time following external (EX-), endoscopic (EN-), and transcanalicular multidiode laser (TC-) dacryocystorhinostomy (DCR) and to evaluate the relationship between culture positivity and surgical success. We further performed antibiotic sensitivity analyses for lacrimal sac culture samples. Methods: A total of 90 patients with primary acquired nasolacrimal duct obstruction were recruited and divided into E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…61 However, Balikoglu-Yilmaz et al reported no significant association between pre-operative conjunctival and lacrimal sac bacterial growth and the success rate of DCR. 62 Considering these divergent opinions, in the END-DCR series reported in our study, all publications describe the application of ocular antibiotics and in 64% was associated with systemic antibiotic therapy but with no significant influence on the surgical outcome (p ¼ 0.45). Considering EXT-DCR, 50% of studies described the use of systemic antibiotics, 67% ocular antibiotics and 17% nasal antibiotics; only 1 EXT-DCR study avoided any specific type of local or systemic therapy.…”
Section: Discussionmentioning
confidence: 76%
“…61 However, Balikoglu-Yilmaz et al reported no significant association between pre-operative conjunctival and lacrimal sac bacterial growth and the success rate of DCR. 62 Considering these divergent opinions, in the END-DCR series reported in our study, all publications describe the application of ocular antibiotics and in 64% was associated with systemic antibiotic therapy but with no significant influence on the surgical outcome (p ¼ 0.45). Considering EXT-DCR, 50% of studies described the use of systemic antibiotics, 67% ocular antibiotics and 17% nasal antibiotics; only 1 EXT-DCR study avoided any specific type of local or systemic therapy.…”
Section: Discussionmentioning
confidence: 76%
“…A study on conjunctival and lacrimal sac specimens before and after dacryocystorhinostomy, with Staphylococcus aureus being the primarily isolated bacterium, revealed a decreased growth rate and a change in antibiotic sensitivity following external, endoscopic and trans-canalicular multidiode laser surgery. These findings may be extrapolated to show the benefits of laser surgery in other nasal and paranasal cavity disorders ( 38 ).…”
Section: Lasers and Biofilmsmentioning
confidence: 88%
“…S taphylococcus aureus, Streptococcus pneumoniae y Haemophilus influenzae son los patógenos que con mayor frecuencia causan las conjuntivitis bacterianas (1)(2)(3). Sin embargo, existe una amplia variedad de bacterias oportunistas, especialmente de la microbiota de piel y mucosas, que está asociada con infecciones de la superficie ocular, y dentro de las cuales el Staphylococcus epidermidis es la especie de estafilococos coagulasa negativos (ecn) más identificada (>50 %) en la conjuntivitis bacteriana 75 % (4,5).…”
Section: Introductionunclassified